2012
DOI: 10.3389/fpsyt.2012.00087
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Non-Invasive Brain Stimulation Therapies and Cardiovascular Risk: Implications for the Treatment of Major Depressive Disorder

Abstract: Major depressive disorder (MDD) and cardiovascular diseases are intimately associated. Depression is an independent risk factor for mortality in cardiovascular samples. Neuroendocrine dysfunctions in MDD are related to an overactive hypothalamus-pituitary-adrenal (HPA) axis and increased sympathetic activity. Novel intervention strategies for MDD include the non-invasive brain stimulation (NIBS) techniques such as repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…Nonetheless, the effects of rTMS and tDCS on the HPA and SAM axes, which are directly linked to the neuroimmunological response, have been evaluated in healthy volunteers and neuropsychiatric disorders. On this matter, two recent reviews (Sampaio et al 2012; Schestatsky et al 2013) found mixed evidence regarding possible neuromodulatory effects on these systems, with positive results obtained from studies generally employing designs in which participants were submitted to physiological or psychological stress (e.g., (Brunoni et al 2013c)). Using data from SELECT-TDCS, we observed that tDCS-only and combined with sertraline did not modulate heart rate variability, a marker of sympathetic/parasympathetic activity, throughout the trial (Brunoni et al 2013a) and also, that these therapies had no specific antidepressant effects on vegetative symptoms (Brunoni et al, in press), as similarly observed in another tDCS trial (Alonzo et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the effects of rTMS and tDCS on the HPA and SAM axes, which are directly linked to the neuroimmunological response, have been evaluated in healthy volunteers and neuropsychiatric disorders. On this matter, two recent reviews (Sampaio et al 2012; Schestatsky et al 2013) found mixed evidence regarding possible neuromodulatory effects on these systems, with positive results obtained from studies generally employing designs in which participants were submitted to physiological or psychological stress (e.g., (Brunoni et al 2013c)). Using data from SELECT-TDCS, we observed that tDCS-only and combined with sertraline did not modulate heart rate variability, a marker of sympathetic/parasympathetic activity, throughout the trial (Brunoni et al 2013a) and also, that these therapies had no specific antidepressant effects on vegetative symptoms (Brunoni et al, in press), as similarly observed in another tDCS trial (Alonzo et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group (Brunoni et al, 2013a) observed HF HRV to increase during anodal tDCS while participants viewed negative-valence images, indicating that tDCS may counterbalance the physiological stress associated with viewing of negative images. In this regard we recently proposed -in a systematic review (Sampaio et al, 2012) -that acute tDCS effects on cardiovascular activity occur during stress-induced paradigms.…”
Section: Main Findingsmentioning
confidence: 98%
“…Moreover, tDCS is an intervention with minimal, systemic side-effects (Brunoni et al, 2010). In fact, acute tDCS seems to have either no or favorable effects on sympathovagal balance (Sampaio et al, 2012;Vandermeeren et al, 2010;Montenegro et al, 2011;Brunoni et al, 2013a) -the latter effects possibly due to the role of the prefrontal cortex in inhibiting cardio-acceleratory circuitry, thereafter increasing vagal activity (Thayer et al, 2010). Therefore, our hypothesis was that reductions in HRV following antidepressant drugs and increases in HRV following tDCS would demonstrate the adverse effects of pharmacological vs. non-pharmacological treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Heart rate variability is not the only measurement that highlights the link between components of MetS and MHDs; non-invasive brain stimulation strategies can improve depressive symptoms in patients with depression or bipolar disorder [226] and may be effective in reducing HPA activity [227]. …”
Section: Reduction Of the Heart Rate Variabilitymentioning
confidence: 99%